Nodular Lymphocyte Predominant Hodgkin Lymphoma: A Single Center Experience - Oral, Kübra; Uysal, Ayse (My University, 2025)
Aim: Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) is a rare subtype of lymphoma classified within Hodgkin lymphomas. Often the diagnosis is made at an early stage. Treatment varies according to the stage of the disease and the underlying prognostic factors. Because of cluster of differentiation 20 expression, rituximab-based agents can be used for treatment. In this study, we aimed to present the demographic, treatment, and survival data of patients with NLPHL in the context of the existing literature. Methods: In our study, demographic characteristics, laboratory findings, disease stage, and treatments administered to patients diagnosed with NLPHL between 2012 and 2024 were evaluated. Results: Of the 13 patients enrolled in the study, seven were male, and the median age was 44 years. Of the patients, eight were in the early stage and five were in the advanced stage. One patient had liver involvement, three had splenic involvement, seven had subdiaphragmatic involvement, and four had a bulky mass. Rituximab was added to the treatment regimens of six patients. Progression was observed in two patients. One patient died from Coronavirus disease 2019-related pneumonia. While the 2-year and 5-year overall survival of our patients were both 92%, progression-free survival was 100% at 2 years and 45.5% at 5 years. Conclusion: NLPHL is a rare condition that, despite its generally favorable prognosis, requires effective treatment because of the risk of recurrence and transformation into diffuse large B-cell lymphoma (DLBCL). Although data on the transformation of subdiaphragmatic involvement into DLBCL exist in the literature, information on disease progression is lacking.
Keywords: Overall survival; progression free survival; Nodular lymphocyte-predominant hodgkin lymphoma